2011
DOI: 10.3832/ifor0591-004
|View full text |Cite
|
Sign up to set email alerts
|

Is methane released from the forest canopy?

Abstract: Laboratory experiments show that rates of CH4 emission from plant material depend exponentially on temperature and linearly on UV irradiance. The UV irradiance shall be spectrally weighted and shorter wavelengths results in higher CH4 emissions. Global upscaling models for estimating aerobic CH4, based on lab results, have be conducted with varying results, but until now field measurements based on profile and eddy covariance measurements have failed to show CH4 emissions from forest canopies. To detect CH4 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Night‐time measurements in a temperate beech forest indicated a small CH 4 emission from canopy leaves (Mikkelsen et al . ), and it seems appropriate to scale the dark emission with mass and temperature (Bruhn et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Night‐time measurements in a temperate beech forest indicated a small CH 4 emission from canopy leaves (Mikkelsen et al . ), and it seems appropriate to scale the dark emission with mass and temperature (Bruhn et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…Early field work did not report enough details about the environmental conditions. We have attempted to provide explanations for potential impacts that may have occurred in some studies (Table S1); for instance, an impact from UV radiation might have occurred at experimental sites with high elevations, thereby affecting the observation of CH 4 emissions (Cao et al, 2008;Mikkelsen et al, 2011). Furthermore, results have shown that CH 4 concentrations are greater in upland forests than in lowland forests (do Carmo et al, 2006;Sinha et al, 2007).…”
Section: Plantsmentioning
confidence: 99%
“…At the ecosystem scale, all studies applying chamber‐based measurements (Sanhueza and Donoso 2006, Cao et al 2008, Wang et al 2009a) could confirm CH 4 release in an anaerobic atmosphere at least during some periods. On the other hand, studies of vertical profiles of [CH 4 ] both indicate CH 4 release (Mikkelsen et al 2011) and no CH 4 release (Bowling et al 2009). Diel profiles of [CH 4 ] in both temperate and tropical forest systems indicated CH 4 release (Sinha et al 2007), whereas eddy covariance CH 4 measurements over a Californian pine plantation did not (Smeets et al 2009).…”
Section: Experimental Validation Of the Phenomenonmentioning
confidence: 99%